2008
DOI: 10.1111/j.1467-8659.2008.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Topology‐Preserving λ2‐based Vortex Core Line Detection for Flow Visualization

Abstract: We propose a novel vortex core line extraction method based on the λ 2 vortex region criterion in order to improve the detection of vortex features for 3D flow visualization. The core line is defined as a curve that connects λ 2 minima restricted to planes that are perpendicular to the core line. The basic algorithm consists of the following stages: (1) λ 2 field construction and isosurface extraction; (2) computation of the curve skeleton of the λ 2 isosurface to build an initial prediction for the core line;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The main idea is shown in Figure 2, and is similar to the horse-shoe vortex shown in Schafhitzel et al 9 The flow is easy to describe, although the equations are a bit complicated. Some software is available on the Internet.…”
Section: A Limitation Of Existing Higher Order Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The main idea is shown in Figure 2, and is similar to the horse-shoe vortex shown in Schafhitzel et al 9 The flow is easy to describe, although the equations are a bit complicated. Some software is available on the Internet.…”
Section: A Limitation Of Existing Higher Order Methodsmentioning
confidence: 87%
“…This phenomenon was exhibited in a steady flow, but obviously anything that happens in a steady flow can also happen in an unsteady flow. Schafhitzel et al 9 evaluate several higher-order methods empirically.…”
Section: Discussionmentioning
confidence: 99%
“…This might amplify noise in the data and introduce further errors. We found that the λ 2 -criterion is more established among blood flowspecific works [4,36,39] and decided to use it as well. The necessary eigenvalue analysis of the Jacobian matrix is done on the GPU using Cardano's method [21].…”
Section: Discussionmentioning
confidence: 99%
“…[19], the Q-criterion by Hunt [18], the reduced velocity by Sujudi and Haimes [40], cores of swirling particle motion by Weinkauf et al [45], normalized helicity by Levy et al [23], vorticity and torsion. Schafhitzel et al state that the λ 2 -criterion is most effective and most reliable [36]. Global algorithms return more precise results to the price of higher computation times.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to finding extremal lines of vortices following (minimal) pressure scalars and vorticity vectors, named the "predictor-corrector" technique, was developed by Singer and Banks [19], [20], [21]. It was extended by Ertl et al [3], [22], [23], [24], where the 2 criterion is used instead of pressure, and vorticity vectors are retained for vortex directions.…”
Section: Background On Vortex Extraction Techniquesmentioning
confidence: 99%